Age of air from ACE-FTS measurements of sulfur hexafluoride - L. N. Saunders; K. A. Walker; G. P. Stiller; T. von Clarmann; F. Haenel; H. Garny; H. Garny; H. Bönisch; C. D. Boone; A. E. Castillo; A. Engel; J. C. Laube; et al. (Atmospheric Chemistry and Physics)
Climate models predict that the Brewer–Dobson circulation (BDC) will accelerate due to tropospheric warming, leading to a redistribution of trace gases and, consequently, to a change of the radiative properties of the atmosphere. Changes in the BDC are diagnosed by the so-called “age of air”, that is, the time since air in the stratosphere exited the troposphere. These changes can be derived from a long-term observation-based record of long-lived trace gases with increasing concentration in the troposphere, such as sulfur hexafluoride (SF6). The Atmospheric Chemistry Experiment Fourier Transform Spectrometer (ACE-FTS) provides the longest available continuous time series of vertically resolved SF6 measurements, spanning 2004 to the present. In this study, a new age-of-air product is derived from the ACE-FTS SF6 dataset. The ACE-FTS product is in good agreement with other observation-based age-of-air datasets and shows the expected global distribution of age-of-air values. Age of air from a chemistry–climate model is evaluated, and the linear trend of the observation-based age of air is calculated in 12 regions within the lower stratospheric midlatitudes (14–20 km, 40–70°) in each hemisphere. In 8 of 12 regions, there was not a statistically significant trend. The trends in the other regions, specifically 50–60 and 60–70° S at 17–20 km and 40–50° N at 14–17 and 17–20 km, are negative and significant to 2 standard deviations. This is therefore the first observation-based age-of-air trend study to suggest an acceleration of the shallow branch of the BDC, which transports air poleward in the lower stratosphere, in regions within both hemispheres.